Penilaian Kualitas dan Risiko Pembiayaan Bank Syari'ah - Jefri, Gio Vani; Nurnasrina, Nurnasrina; Syahfawi, Syahfawi (MUI Kota Pekanbaru, 2023)
The quality of productive assets plays a significant role in the success of Islamic banking, not just a mere function. Islamic banks consistently measure their performance by referring to the standard of productive asset quality as a benchmark. The prosperity of an Islamic bank's business substantially depends on its ability to manage investments by adhering to two main principles: the prudence principle and the Sharia principle. The aim of this research is to conduct a comprehensive evaluation of the quality and risks in Islamic bank financing. To face the complexity and dynamics of the Islamic banking world, a qualitative approach was used. The research method is based on the post-positivism philosophical foundation, which views social reality as a whole, dynamic, complex, meaningful, and colored by interactive relationships.